"Building as machine": mental image of combined cycle power plants workers. Issue 1 (16th July 2021) - Rezaee, Mohammad; Eghbali, Seyed Rahman
Abstract : Purpose: This paper aims to interpret the workers' perception of combined cycle power plants through visual qualities. Design/methodology/approach: In this qualitative research landscape image, the sketching technique is applied as a data collection method to extract participants' mental images by asking them to draw sketches. The resulted sketches besides obtained verbal and written data were analyzed and coded in three stages to explain the workers' perception. Visual qualities were studied as a mean which made it possible to interpret the workers' perception of their workplace. Findings: Careful analysis of the gathered data and the emerged concepts via open coding identify four axial categories of the concepts forming the workers' perception of the power plants: "inconsistency with nature, " "emphasis on function and product, " "health and environmental threats" and "interpretation of the built form as a mass instead of space." These four categories support the core category of the proposed theory which is "perceiving building as the machine." This phrase explains how workers perceive power plants as machines, not as supportive and lively environments. This is followed by consequences, "precedence of building over human" is prominent among them. Originality/value: In the relevant body of literature, visual impact and visual perception of conventional thermal power plants are largely missed, as well as visual relation to environment focusing on a single building or groups of adjacent buildings. This paper covers both areas via asking for sketches as a data collection method, in addition, to interview the participants to clarify their mental image of the work environment.